1972
DOI: 10.1128/aem.23.5.914-918.1972
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Rabies Virus Inactivated by β-Propiolactone, Acetylethyleneimine, and Ionizing Irradiation

Abstract: Ionizing radiation, f-propiolactone, and acetylethyleneimine were compared for their ability as virus-inactivating agents for the preparation of rabies vaccine. Each agent reduced viral infectivity exponentially; ionizing radiation also destroyed viral hemagglutinin. The vaccine prepared by ionizing radiation was equal or superior to that prepared by f3-propiolactone in its ability to protect mice from rabies infection. The acetylethyleneimine-treated vaccine was a less potent immunogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Neither study identified the minimum length of time required for complete inactivation of IHNV infectivity. For comparison, rabies virus treated with 4 to 8 m m BPL or 10 m m BEI is inactivated within 0.5–6 h (Wiktor, Aaslestad & Kaplan 1972; Larghi, Savy, Negel & Rodriguez 1976; Larghi & Nebel 1980). However, this incubation time does not ensure the absence of live residual rabies virus when the innocuity of the vaccine is measured using live animals (Mitchell, Everest & Anderson 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Neither study identified the minimum length of time required for complete inactivation of IHNV infectivity. For comparison, rabies virus treated with 4 to 8 m m BPL or 10 m m BEI is inactivated within 0.5–6 h (Wiktor, Aaslestad & Kaplan 1972; Larghi, Savy, Negel & Rodriguez 1976; Larghi & Nebel 1980). However, this incubation time does not ensure the absence of live residual rabies virus when the innocuity of the vaccine is measured using live animals (Mitchell, Everest & Anderson 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports (9,13,14) on the preparation of experimental vaccines with high levels of immunogenicity have described the inactivation of rabies virus. The effects of various physical and chemical methods of inactivation have been compared by complement fixation, hemagglutination, and infectivity assays.…”
Section: Resultsmentioning
confidence: 99%
“…BPL inactivates viral RNA by alkylation of guanine to form 7- (2-carboxyethyl)guanine (25). However, BPL has also been found to alter viral surface proteins associated with hemagglutination and target cell attachment (31). The rotavirus outer capsid is composed of two major proteins, vp4 and vp7 (3,16).…”
Section: Discussionmentioning
confidence: 99%